DEVELOPING GROWTH MINDSET IN SENIOR PAUD LEADERSHIP: ADAPTATION STRATEGIES FOR DEEP LEARNING CURRICULUM IN DIGITAL ERA - Bunayyah, Siti; Zhafirah, Anisah; Rohma, Naili; Hasibuan, Rahma (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2025)
The digital era has brought fundamental transformations to early childhood education (PAUD), demanding responsive curriculum adaptation and leadership. This study aims to analyze the role of the growth mindset in senior PAUD leadership in adapting the deep learning curriculum in the digital era through a systematic literature review. The findings indicate that a growth mindset serves as a crucial catalyst enabling PAUD leaders to implement transformational leadership and managerial functions effectively to address digital challenges, such as teachers’ low digital literacy, limited technological infrastructure, and policy gaps. The resulting adaptation strategies include enhancing teachers’ digital competencies, providing adequate infrastructure, and integrating holistic, play-based learning principles into the deep learning curriculum. The implications offer practical guidance for developing PAUD leadership and theoretical contributions to aligning growth mindset, transformational leadership, and curriculum innovation within PAUD settings. Keywordl: growth mindset; curriculum; leadership   Abstrak Era digital telah membawa transformasi mendasar pada pendidikan anak usia dini (PAUD), yang menuntut adaptasi kurikulum dan kepemimpinan yang responsif. Studi ini bertujuan untuk menganalisis peran pola pikir pertumbuhan (growth mindset) dalam kepemimpinan senior PAUD dalam mengadaptasi kurikulum pembelajaran mendalam di era digital melalui tinjauan literatur sistematis. Temuan menunjukkan bahwa pola pikir pertumbuhan berfungsi sebagai katalis penting yang memungkinkan para pemimpin PAUD untuk menerapkan kepemimpinan transformasional dan fungsi manajerial secara efektif untuk mengatasi tantangan digital, seperti rendahnya literasi digital guru, keterbatasan infrastruktur teknologi, dan kesenjangan kebijakan. Strategi adaptasi yang dihasilkan meliputi peningkatan kompetensi digital guru, penyediaan infrastruktur yang memadai, dan pengintegrasian prinsip-prinsip pembelajaran holistik berbasis permainan ke dalam kurikulum pembelajaran mendalam. Implikasinya menawarkan panduan praktis untuk mengembangkan kepemimpinan PAUD dan kontribusi teoritis untuk menyelaraskan pola pikir pertumbuhan, kepemimpinan transformasional, dan inovasi kurikulum dalam lingkungan PAUD. Kata kunci: Kata kunci: pola pikir berkembang; kurikulum; kepemimpinan